STRATEGI PEMASARAN PASTA UBI JALAR PADA PT GALIH ESTETIKA INDONESIA DI KECAMATAN CILIMUS KABUPATEN KUNINGAN JAWA BARAT - Pratama, Muhammad Faza; Setiawati, Indah (Universitas Galuh, 2023)
PT Galih Estetika Indonesia is the first company in Indonesia engaged in processing sweet potatoes with the main product being pasta. This study aims to describe the STP strategy, marketing mix and marketing constraints of sweet potato paste products at PT Galih Estetika Indonesia. This research was conducted with descriptive method. The research data were obtained through observation and in-depth interviews with the management of PT Galih Estetika Indonesia. Marketing constraint data is processed using fishbone analysis. Based on the results of STP analysis and marketing mix, sweet potato pasta products from PT Galih Estetika Indonesia can compete with competitors and have a broad market such as Korean and Japanese people who adopt a healthy lifestyle and understand the ingredients of sweet potato. However, marketing at PT Galih Estetika Indonesia still has problems at some time in the form of product color specification discrepancies which result in complaints from buyers. These obstacles arise due to the lack of effectiveness of employees at PT Galih Estetika Indonesia